2011
DOI: 10.1007/s00228-011-1013-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of CYP2C9 gene polymorphisms on response to glibenclamide in type 2 diabetes mellitus patients

Abstract: The type 2 diabetes mellitus patients participating in this study with variant genotypes of CYP2C9 were found to respond better to treatment with glibenclamide than those with the normal genotype. The variant genotype CYP2C9 *1/*3 did not significantly influence the hypoglycemic adverse effects among those patients on long-term glibenclamide treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
32
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 19 publications
1
32
0
6
Order By: Relevance
“…Of importance was the observation that insulin inhibits increased expression of CYP4A in diabetic rats. There are a number of studies associating sEH polymorphisms with insulin resistance in T2DM; however, there seems to be no association of variant alleles of CYP2C9, CYP2C8 or CYP2CJ2 in humans with either T1DM or T2DM (Surendiran et al, 2011). Further studies are necessary to determine the role of CYP2C and CYP4A AA metabolites in the function of β-cells and exocrine islet function in GSIS in hyperglycemia.…”
Section: Eicosanoids and Mets Diseasesmentioning
confidence: 99%
“…Of importance was the observation that insulin inhibits increased expression of CYP4A in diabetic rats. There are a number of studies associating sEH polymorphisms with insulin resistance in T2DM; however, there seems to be no association of variant alleles of CYP2C9, CYP2C8 or CYP2CJ2 in humans with either T1DM or T2DM (Surendiran et al, 2011). Further studies are necessary to determine the role of CYP2C and CYP4A AA metabolites in the function of β-cells and exocrine islet function in GSIS in hyperglycemia.…”
Section: Eicosanoids and Mets Diseasesmentioning
confidence: 99%
“…CYP2C9 polymorphism displays a better response to anti-diabetic medicine in T2DM patients [150; 151], but carries a high risk of hypoglycemia, raising the possibility of a pharmacogenetic interaction [152]. Increased prevalence of the CYP2C8*4 mutation has been found in T2DM patients [153].…”
Section: Eicosanoids and Diabetesmentioning
confidence: 99%
“…In 2011, Surendiran et al found a significant association between CYP2C9*1/*1 genotypes and the lack of control of diabetic Hindi patients receiving combined therapy with metformin and glibenclamide [4].…”
mentioning
confidence: 99%
“…This disease has a prevalence of 14%, and it is calculated that in Mexico there are 8 million diabetic patients; 85% of them are treated with oral hypoglycemics, mainly sulfonylureas, metformin, or both [3]. Hypoglycemic agents like glibenclamide are metabolized mainly by CYP2C9 [4]. Glibenclamide and a combination of this with metformin are the best-selling glycemia-control drugs in Mexico, and this particular market has shown a general rising trend, with an increase of 141% between 1999 and 2003 [5].…”
mentioning
confidence: 99%